PEMBENTUKAN POS KESEHATAN PESANTREN DAN SOSIALISASI BUKU KESEHATAN SANTRI - Ani Laila; Okta Vitriani; Fathunikmah Fathunikmah (Jurusan Kebidanan Poltekkes Kemenkes Riau, 2022)
Islamic boarding schools in Indonesia have many classic problems, namely about the health of students and problems with disease. Health problems and diseases in Islamic boarding schools rarely receive good attention from the pesantren residents themselves and the community and also the government. Pesantren itself is a sub-culture where Islamic boarding schools have their own culture that is different from society in general (Ikhwanuddin, 2013). The development and progress of pesantren is sometimes not supported by adequate facilities and infrastructure. The number of rooms that are not in accordance with the number of students, as well as the awareness of pesantren residents about health are still below the standard of Clean and Healthy Living Behavior. Based on the explanation above, it can be concluded that the problems that are often faced by Islamic boarding schools related to health are poor hygiene and sanitation in Islamic boarding schools and the low health awareness and healthy behavior of the students. Therefore, it is necessary to carry out continuous coaching by involving students and pesantren residents. The Ummahatul Mukminin Islamic Boarding School is one of the special Islamic boarding schools for female students which was only established in 2019 on Al Ikhlas Street, Pekanbaru city. The new cottage has 3 classes of wustho (junior high school) and 1 senior high school . Based on the team's observations, it was not uncommon for students to have complaints such as itching of the skin and hair, coughing, stomach pain, dizziness and others. This fact prompted the community service team of the Midwifery D3 study program to feel moved to make changes to the pesantren environment and its surroundings. The pesantren really hopes for the transfer of science and technology to increase independence and clean and healthy living behavior of the students so that later after graduating from the pesantren they have life skills, in addition to religious knowledge, as a provision for them to live healthy in society. Keywords: Islamic boarding schools, clean and healthy lifestyle